Communication Strategy of Investigators in Handling Crimes Based on Restorative Justice in the Criminal Investigation Unit of Sukoharjo Resort Police - Basuki Wahyu Utomo; Sri Hastjarjo; Andre Rahmanto (Journal of Social Interactions and Humanities, 2023)
The police formulated an alternative solution to answer the development of legal needs in Indonesia. Now, the handling of criminal offenses can be carried out by police investigators based on restorative justice to fulfill a sense of justice for all parties. This study aims to describe the communication strategy of investigators in handling criminal offenses based on restorative justice and the obstacles they experience. This research uses interpretive paradigm research methodology, qualitative approach, in-depth interview method, and descriptive research type. The research population included investigators at the Sukoharjo Resort Police Criminal Investigation Unit with three informant samples consisting of key, main and supporting informants. The results showed that the communication strategy carried out by investigators in handling criminal offenses based on restorative justice is a face-toface meeting (case title) to carry out open discussions with the aim of repairing relationships with solutions that are fair to all parties. The obstacle is that each party defends their interests and feels that the chosen solution is the fairest decision